2008
DOI: 10.3390/ijms9101989
|View full text |Cite
|
Sign up to set email alerts
|

Accelerator Analysis of Tributyltin Adsorbed onto the Surface of a Tributyltin Resistant Marine Pseudoalteromonas sp. Cell

Abstract: Tributyltin (TBT) released into seawater from ship hulls is a stable marine pollutant and obviously remains in marine environments. We isolated a TBT resistant marine Pseudoalteromonas sp. TBT1 from sediment of a ship's ballast water. The isolate (10 9.3 ± 0.2 colony-forming units mL -1 ) adsorbed TBT in proportion to the concentrations of TBTCl externally added up to 3 mM, where the number of TBT adsorbed by a single cell was estimated to be 10 8.2 . The value was reduced to about one-fifth when the lysozyme-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Such drastic alterations in cell size are a protective mechanism in several bacteria subjected to heavy-metal and organotin stress (Mimura et al, 2008;Naik and Dubey, 2011;Shamim et al, 2013). A similar response was observed in P. aeruginosa strain 4EA under the stress of lead (Naik and Dubey, 2011).…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Such drastic alterations in cell size are a protective mechanism in several bacteria subjected to heavy-metal and organotin stress (Mimura et al, 2008;Naik and Dubey, 2011;Shamim et al, 2013). A similar response was observed in P. aeruginosa strain 4EA under the stress of lead (Naik and Dubey, 2011).…”
Section: Discussionmentioning
confidence: 62%
“…The role of pyochelin in conferring resistance to TPT has also been demonstrated in Pseudomonas aeruginosa (Sun et al, 2006). Both pyochelin and pyoverdine siderophores have also been implicated in lead resistance in P. aeruginosa strain 4EA (Naik and Dubey, 2011). Similarly, TBTCl-degrading marine Pseudomonas spp.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Concentrations as high as 500 ng/L have been detected in coastal waters (Alzieu et al, 1989). Tributyltin is considered an endocrine disruptor (Mimura et al, 2008) to aquatic organisms due to its ability to produce male sexual characteristics in female abalones (a type of sea snail) at 100 ng/L (Horiguchi et al, 2002) and gastropods (also a type of snail) (Horiguchi, 2006). Numerical standards for tributyltin exist in states such as Colorado, which were established from EPA's National Recommended Water Quality Criteria.…”
Section: Diazinonmentioning
confidence: 98%
“…TPT therefore contaminates the marine environment during painting and hosing activities in the form of paint particles at the harbor/dockyard. Although banned in some countries on vessels <25 m in length , studies have found high concentration of organotins (TPT and TBT (tributyltin)) in tissues of marine mammals, their presence has been linked to imposex formation in mollusks and mass mortalities of marine mammals , and in human, consumption of seafood is thought to be the possible source of TPT , hence, a need to treat shipyard process wastewater free from TPT before discharge into the marine environment.…”
Section: Introductionmentioning
confidence: 99%